2009
DOI: 10.1002/num.20446
|View full text |Cite
|
Sign up to set email alerts
|

Cosine expansion‐based differential quadrature algorithm for numerical solution of the RLW equation

Abstract: The differential quadrature method based on cosine expansion is applied to obtain numerical solutions of the RLW equation. The propagation of single solitary wave is studied to validate the efficiency of the algorithm. Then, test problems including interaction of two and three solitary waves, undulation, and evolution of solitary waves are implemented. Solutions are compared with earlier results. Discrete conservation quantities are computed for test experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Shu (2000) proposed the most general approach for finding the weighting coefficients by using Lagrange's interpolation as base functions. Recently, in literature the most frequently used differential quadrature procedures to solve one and two-dimensional differential equations are Lagrange interpolation polynomials-based differential quadrature method (PDQM), CDQM and other methods (Mittal and Jiwari, 2009, 2011Jiwari et al, 2012,a, b;Dag et al, 2010;Korkmaz, 2009;Korkmaz and Dağ, 2008;Korkmaz and Dağ, 2009a, b, c;Verma et al, 2014;Saka, 2009;Korkmaz, 2010;Shao and Wu, 2012;Dehghan and Nikpour, 2013b).…”
Section: Cdqmmentioning
confidence: 99%
“…Shu (2000) proposed the most general approach for finding the weighting coefficients by using Lagrange's interpolation as base functions. Recently, in literature the most frequently used differential quadrature procedures to solve one and two-dimensional differential equations are Lagrange interpolation polynomials-based differential quadrature method (PDQM), CDQM and other methods (Mittal and Jiwari, 2009, 2011Jiwari et al, 2012,a, b;Dag et al, 2010;Korkmaz, 2009;Korkmaz and Dağ, 2008;Korkmaz and Dağ, 2009a, b, c;Verma et al, 2014;Saka, 2009;Korkmaz, 2010;Shao and Wu, 2012;Dehghan and Nikpour, 2013b).…”
Section: Cdqmmentioning
confidence: 99%
“…Benjamin et al [2] showed the similarity of wave solutions of the RLW equation to the wave solutions of the more widely known Korteweg-de Vries (KdV) equation. RLW equation has been solved by various numerical method including finite difference method [3][4][5], collocation method [7][8][9][10][11][12], Galerkin method [13][14][15][16][17][18][19][20][21][22], and Quadrature method [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The Adomian decomposition method is another method to design some of the exact solitary wave solutions of the generalized form of the BBM equation [6]. Besides the analytical and exact solutions of the BBM equation, many numerical techniques from different families are developed and implemented for the numerical solutions to various evolution problems for the BBM equation [7,8,9]. The symmetric BBM equation is defined by Seyler and Fenstermacher [10] to describe ion acoustic and space charge waves in the weakly nonlinear sense.…”
Section: Introductionmentioning
confidence: 99%